Assessment of efficacy and safety of daclatasvir, sofusbuvir and ribavirin regimen for 12 weeks as compared to daclatasvir and sofusbuvir combination regimen for 24 weeks in decompensated cirrhotic patients due to hepatitis C virus genotype 3 infection - Tyagi, Ayush; Kumar, Vinay; Giri, Richa (International Journal of Advances in Medicine, 2022)
Background: Assessment of efficacy and safety of daclatasvir+sofosbuvir+ribavirin (DCV+ SOF+ RBV) for 12 weeks as compare to daclatasvir and sofusbuvir for 24 weeks in decompensated cirrhotic patients due to hepatitis C virus (HCV) genotype 3 infection. Methods: An observational, prospective, COHORT study over 1 year, in decompensated cirrhosis due to G3-HCV infected adult patients. Treatment was a combination of sofosbuvir 400 mg/day+daclatasvir 60 mg/day, with or without a weight-adjusted dosing of ribavirin for 12 or 24 weeks. The primary efficacy endpoint was sustained virologic response rates 12 weeks after therapy (SVR 12). The primary safety endpoint was treatment withdrawal rates secondary to severe adverse events. Results: The 32 patients were screened and 2 were excluded, one patient due to associated HBV+, one patient due to severe anemia. 30 patients were randomized. All 30 randomized patients were divided into two groups. Group 1 was given SOF+DCV+RBV for 12 weeks while group 2 patients were given SOF+DCV for 24 weeks. 81.8% of the participants in the group1 achieved SVR 12. The 90.9% of the participants in the group 2 achieved SVR12 (p=1). No other patient or treatment basal variables influenced the treatment effectiveness. No patient treatment withdrawal secondary to severe adverse events was observed. Conclusions: Both the regimen SOF+DCV with or without RBV are highly efficacious and safe. Addition of RBV can reduce the treatment duration to 12 weeks, and it will further improve compliance and more convenient for the patients.